2023
DOI: 10.35848/1347-4065/aceb44
|View full text |Cite
|
Sign up to set email alerts
|

Guideline for improving spatial resolution in direct-modulation Brillouin optical correlation-domain reflectometry

Abstract: We investigate the spatial resolution of direct-modulation Brillouin optical correlation-domain reflectometry (BOCDR) by exploring the impact of modulation amplitude and frequency. Our findings reveal that optimal resolution improvement is attained through an initial increase in modulation amplitude, followed by modulation frequency adjustment. These insights provide a basic guideline for enhancing the spatial resolution in direct-modulation BOCDR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…To date, no technique (except for the one we have developed) has been reported that enables low-cost temperature measurement near the tip of a commercially available optical fiber without necessitating any specialized processing. Alternatively, distributed sensing techniques capable of providing longitudinal temperature variations along the fiber have been explored, [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] but these too come with a high cost.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, no technique (except for the one we have developed) has been reported that enables low-cost temperature measurement near the tip of a commercially available optical fiber without necessitating any specialized processing. Alternatively, distributed sensing techniques capable of providing longitudinal temperature variations along the fiber have been explored, [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] but these too come with a high cost.…”
mentioning
confidence: 99%
“…Brillouin-based single-end-access distributed sensors can be categorized into three types: Brillouin optical time-domain reflectometry (BOTDR), [12][13][14] Brillouin optical frequency-domain reflectometry (BOFDR), 15) and BOCDR. [16][17][18][19][20][21][22][23][24][25][26] Each technique has its own merits and demerits, and here we focus on BOCDR.…”
mentioning
confidence: 99%